2018
DOI: 10.1016/j.celrep.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

From Hyper- to Hypoinsulinemia and Diabetes: Effect of KCNH6 on Insulin Secretion

Abstract: Graphical Abstract Highlights d KCNH6 regulates insulin secretion and glucose hemostasis in humans and mice d KCNH6 dysfunction causes a phenotype from hyper-to hypoinsulinemia and diabetes d KCNH6 dysfunction increases intracellular calcium levels and hyperinsulinemia d Chronic elevation of intracellular calcium causes b cell loss and hypoinsulinemia In Brief Yang et al. show that KCNH6 plays a key role in insulin secretion and glucose hemostasis in humans and mice. Dysfunction of KCNH6 results in a hyperinsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…12 We also found that Kcnh6 knockout (KO) or Kcnh6 p. P235L knockin (KI) mice had a phenotype characterized by changing from hypoglycemia with hyperinsulinemia to hyperglycemia with insulin deficiency. 12 These data imply that KCNH6 may play an important role in insulin secretion and glucose homeostasis. So, we used the whole-body Kcnh6 knockout model in this study.…”
Section: Discussionmentioning
confidence: 94%
“…12 We also found that Kcnh6 knockout (KO) or Kcnh6 p. P235L knockin (KI) mice had a phenotype characterized by changing from hypoglycemia with hyperinsulinemia to hyperglycemia with insulin deficiency. 12 These data imply that KCNH6 may play an important role in insulin secretion and glucose homeostasis. So, we used the whole-body Kcnh6 knockout model in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Metabolism of glucose depends on a series of electrogenic events including intracellular Ca 2 + influx through the voltage-dependent Ca 2 + channels. In a previous study, we found that intracellular Ca 2 + influx was higher in the Kcnh6 KO mice [17]. Thus, sustained increased cytosolic Ca 2 + induced by the Kcnh6 knockout may be responsible for the ER stress.…”
Section: Discussionmentioning
confidence: 76%
“…Wild-type (Wt) and Kcnh6 knockout mice (KO) were maintained on a C57/BL6 background (Charles River Laboratories China, Beijing, China). Mice with a targeted deletion of Kcnh6 using Transcription activator-like effector nucleases (TALEN) have been previously described [17]. The mice with chow diet were raised in an environment with 45-65 % humidity and 20-24 °C temperature, a 12-hour light/dark cycle, and access to food and water ad libitum.…”
Section: Animals and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, loss-of-function mutants of the voltage-dependent K+ (Kv) channel KCNH6 plays a role in the modulation of insulin secretion. In a loss-of-function KCNH6 mutant in humans and mice, hyper–insulin secretion was observed initially, followed by subsequent hypo–insulin secretion as a result of overstimulation of insulin secretion; in the long-term, endoplasmic reticulum stress, apoptosis, loss of β-cell mass, and subsequent decreased insulin secretion were observed ( 52 ). These reports suggest that the overstimulation of insulin secretion causes β-cell failure in the long-term, which is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%